Dataset "BIFURCATE FLOWER TRUSS: a novel locus controlling inflorescence branching in tomato contains a defective MAP kinase gene" - Thompson, Andrew J.; Kevei, Zoltan; Silva Ferreira, Demetryus; Mohareb, Fady R.; Kurowski, Tomasz (Cranfield University, 2024)
Data underlying manuscript entitled: "Identification and characterisation of bifuricate, a novel locus on chromosome 12 controlling truss branching and flower number in tomato"
Keywords: Plant Developmental and Reproductive Biology